The Phaseolus vulgaris PvTRX1h gene regulates plant hormone biosynthesis in embryogenic callus from common bean - Barraza, Aarón; Cabrera-Ponce, José Luis; Gamboa-Becerra, Roberto; Luna-Martínez, Francisco; Winkler, Robert; Alvarez-Venegas, Raúl (Frontiers in Plant Science, 2015)
Common bean is the most important grain legume in the human diet. Bean improvement efforts have been focused on classical breeding techniques because bean is recalcitrant to both somatic embryogenesis and in vitro regeneration. This study was undertaken to better understand the process of somatic embryogenesis in the common bean. We focused on the mechanisms by which somatic embryogenesis in plants is regulated and the interaction of these mechanisms with plant hormones. Specifically, we examined the role of the gene PvTRX1h, an ortholog of a major known histone lysine methyltransferase in plants, in somatic embryo generation. Given the problems with regeneration and transformation, we chose to develop and use regeneration-competent callus that could be successively transformed. Embryogenic calli of common bean were generated and transformed with the PvTRX1hRiA construction to down-regulate, by RNA interference, expression of the PvTRX1h gene. Plant hormone content was measured by mass spectrometry and gene expression was assessed by q-PCR. Detailed histological analysis was performed on selected transgenic embryogenic calli. It was determined that down-regulation of PvTRX1h gene was accompanied by altered concentrations of plant hormones in the calli. PvTRX1h regulated the expression of genes involved in auxin biosynthesis and embryogenic calli in which PvTRX1h was down-regulated were capable of differentiation into somatic embryos. Also, down-regulation of PvTRX1h showed increased transcript abundance of a gene coding for a second histone lysine methyltransferase, PvASHH2h. Accordingly, the PvTRX1h gene is involved in the synthesis of plant hormones in common bean callus. These results shed light on the crosstalk among histone methyltransferases and plant hormone signaling and on gene regulation during somatic embryo generation.